Ազգային երաժշտական ակունքները Ռոբերտ Ամիրխանյանի վաղ շրջանի երգերում - Աննա Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
В статье представлены две песни в народном и народно-профессиональном жанре композитора Роберта Амирханяна. Созданные в ранний период творчества, песни неоднократно исполнялись на концертных встречах с различными общинами диаспоры. Anna Khachatryan, in this article, expounds Robert Amirkhanyan’s two songs written in folk and ashugh song styles. These songs representing composer’s early creative period have been frequently performed at concerts all over the world in different Armenian communities of Diaspora, while being virtually unknown in Armenia.
Keywords: M Music and Books on Music; Folk, National and Ethnic Music